Haunting legacy Vietnam and the American presidency from Ford to Obama - Kalb, Marvin L.; Kalb, Deborah (Washington, D.C. Brookings Institution Press, 2011)
"Examines how presidential decision making has been influenced by America's defeat in the Vietnam war, studying presidents Ford, Carter, Reagan, George H. W. Bush, Clinton, George W. Bush, and Obama and how they have approached key decisions regarding conflicts while in office"--Provided by publisher.
Ford : finally, the war ends -- Ford and the mini-challenge of the Mayaguez -- Carter, Brzezinski, and Russia's Vietnam -- Reagan, Grenada, Lebanon, and the marines -- Bush I : burying Vietnam -- Clinton : the first baby-boomer president -- Bush II : boots on the ground -- 2004 : the Swift boat Campaign -- Obama : "Afghanistan is not Vietnam" -- "Good enough".
Keywords: Presidents -- United States -- Decision making -- History -- 20th century; Vietnam War, 1961-1975 -- Influence; United States -- Military policy; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-.; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-.